Dynamic functional network reconfiguration underlying the pathophysiology of schizophrenia and autism spectrum disorder. Issue 1 (23rd September 2020) - Fu, Zening; Sui, Jing; Turner, Jessica A.; Du, Yuhui; Assaf, Michal; Pearlson, Godfrey D.; Calhoun, Vince D.
Abstract: The dynamics of the human brain span multiple spatial scales, from connectivity associated with a specific region/network to the global organization, each representing different brain mechanisms. Yet brain reconfigurations at different spatial scales are seldom explored and whether they are associated with the neural aspects of brain disorders is far from understood. In this study, we introduced a dynamic measure called step‐wise functional network reconfiguration (sFNR) to characterize how brain configuration rewires at different spatial scales. We applied sFNR to two independent datasets, one includes 160 healthy controls (HCs) and 151 patients with schizophrenia (SZ) and the other one includes 314 HCs and 255 individuals with autism spectrum disorder (ASD). We found that both SZ and ASD have increased whole‐brain sFNR and sFNR between cerebellar and subcortical/sensorimotor domains. At the ICN level, the abnormalities in SZ are mainly located in ICNs within subcortical, sensory, and cerebellar domains, while the abnormalities in ASD are more widespread across domains. Interestingly, the overlap SZ‐ASD abnormality in sFNR between cerebellar and sensorimotor domains was correlated with the reasoning‐problem‐solving performance in SZ ( r = −.1652, p = .0058) as well as the Autism Diagnostic Observation Schedule in ASD ( r = .1853, p = .0077). Our findings suggest that dynamic reconfiguration deficits may represent a key intersecting point for SZ and ASD. The investigation of brain dynamics at different spatial scales can provide comprehensive insights into the functional reconfiguration, which might advance our knowledge of cognitive decline and other pathophysiology in brain disorders. Abstract : In this study, we found that both schizophrenia and autism have increased whole‐brain dynamic network reconfiguration and increased dynamic network reconfiguration associated with cerebellar and subcortical/sensorimotor domains. Interestingly, the diseases' overlapping abnormality in dynamic network reconfiguration between cerebellar and sensorimotor domains was correlated with the reasoning‐problem‐solving performance in schizophrenia as well as the Autism Diagnostic Observation Schedule in autism. Our findings suggest that dynamic functional connectivity deficits may represent a key intersecting point for schizophrenia and autism.